2003
DOI: 10.5614/itbj.eng.sci.2003.35.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Complex Morphology of Subducted Lithosphere in the Mantle below the Molucca Collision Zone from Non-linear Seismic Tomography

Abstract: Abstract.Results of seismic studies presented in previous publications depict two opposing subducted oceanic lithospheric slabs under the Molucca region. This unique structure is related to the arc-arc collision between the Halmahera and Sangihe arcs. Recently, we have revisited the complex subduction zone structure by employing a non-linear tomographic imaging technique in which 3-D ray tracing has been implemented. We have used P-as well as S-wave arrival times from carefully reprocessed global data set. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…Previous studies of P-wave tomography have also identified a double subduction of the Molucca Sea Plate to depths of ~600 -650 km subducting to the west, and depths of ~250 -400 km subducting to the east. (Puspito et al 1993;Widiyantoro and Hilst 1997;Hafkenscheid et al 2001;Widiyantoro 2003;Amaru 2007;Fan and Zhao 2018). The arch of double subduction in this area is in the uppermost mantle layer with a depth of ~50 km, which is consistent with the geometry of the slab2 model from Hayes et al (2018).…”
Section: Double Subduction Of the Molucca Sea Platesupporting
confidence: 84%
See 2 more Smart Citations
“…Previous studies of P-wave tomography have also identified a double subduction of the Molucca Sea Plate to depths of ~600 -650 km subducting to the west, and depths of ~250 -400 km subducting to the east. (Puspito et al 1993;Widiyantoro and Hilst 1997;Hafkenscheid et al 2001;Widiyantoro 2003;Amaru 2007;Fan and Zhao 2018). The arch of double subduction in this area is in the uppermost mantle layer with a depth of ~50 km, which is consistent with the geometry of the slab2 model from Hayes et al (2018).…”
Section: Double Subduction Of the Molucca Sea Platesupporting
confidence: 84%
“…Meanwhile, the slab that subducts to the east under the Halmahera Arc reaches a depth of 400 km, which is conformable with the results of the study by Widiyantoro and Hilst (1997). This research was later updated by Widiyantoro (2003) who shows that the subducted slab to the west reaches the lower mantle with a folded-looking slab. Huang et al (2015) also detected a high-velocity zone in the form of bipolar subduction.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation